Monitoring longdistance spore dispersal by wind a review - Viljanen-Rollinson, S.L.H.; Parr, E.L.; Marroni, M.V. (New Zealand Plant Protection, 2007)
Collection of meaningful data on long distance dispersal (LDD) of plant pathogens is very difficult because such events are very rare and the strength and locations of pathogen sources are often unknown This review of the different methods that have been deployed examines combinations of meteorological analyses and ground surveys including spore trapping devices collecting rainwater and identifying spores using realtime PCR The relevance of these techniques is discussed in the context of surveillance and monitoring transTasman dispersal of fungal spores